Brand Image and E-Service Quality's Effect on Gen Z's Repurchase Intention: The Mediating Role of E-Trust - Eka Mitariani, Ni Wayan; Salasa Gama, Agus Wahyudi; Widnyani, Ni Made (Politeknik Negeri Semarang, 2024)
E-commerce has experienced rapid development in Indonesia over last few years due to technological developments in the digital era and followed by trends in people”™s lifestyles which are always changing and following technological developments. This research aims to examine consumer preferences or references towards repurchase intention in e-commerce, particularly in relation to brand image, e-service quality, and e-trust as mediators, in light of the phenomena that have been presented, research results that are still inconsistent, and this relationship to increasing repurchase intention. The sample of this study is Gen Z and data were analyzed use PLS. Result of this study found that brand image and E-service quality are not have significant effect on Gen Z's repurchase intention. E-trust has direct effect on Gen Z's repurchase intention. E-trust also have mediating role on effect of brand image and E-service quality toward Gen Z's repurchase intention. This study reveal E-trust has an important role on Gen Z's behavior to repeat their transaction through an e-commerce.